Milk fed : [compact disc, unabridged] a novel - Broder, Melissa (Simon & Schuster Audio, 2021)
A scathingly funny, wildly erotic, and fiercely imaginative story about food, sex, and god from the acclaimed author of The Pisces and So Sad Today. Rachel is twenty-four, a lapsed Jew who has made calorie restriction her religion. By day, she maintains an illusion of existential control, by way of obsessive food rituals, while working as an underling at a Los Angeles talent management agency. At night, she pedals nowhere on the elliptical machine. Rachel is content to carry on subsisting, until her therapist encourages her to take a ninety-day communication detox from her mother, who raised her in the tradition of calorie counting.